A Question of Gender: Gender classification in international research. (September 2022) - Cartwright, Trixie; Nancarrow, Clive
The research community acknowledges that in many countries and cultures there is greater recognition of the diversity of genders with which people identify. In this paper we define and discuss the categories of "sex", "gender" and related categories and how research participants might identify themselves within these categories. We discuss methods researchers use to classify participants. We examine in depth the principal method the research community uses, namely "asking questions", but we also cover techniques based on observation. We evaluate the possible formats of questions – the introductory question posed, the response options, and, where appropriate, offer suggestions. We note the implications for international research, especially in countries where diversity and associated inclusivity are not yet recognised. The need for research in different cultures is recommended. We note the consequences and implications of adopting or not adopting questions that recognise diversity.